Synergistic antitumoral effect of vinblastine and HSV-Tk/GCV gene therapy mediated by albumin-associated cationic liposomes - Faneca, H. (2008)
Despite recent advances in conventional therapeutic approaches for cancer, the frequently observed acquired drug resistance and toxic side effects have limited their clinical application. The main goal of this work was to investigate the combined antitumoral effect of vinblastine with HSV-Tk/GCV "suicide" gene therapy mediated by human serum albumin (HSA)-associated lipoplexes, in mammary adenocarcinoma cells (TSA cells). Our results show that, among the different lipoplex formulations tested, HSA-associated complexes prepared from EPOPC:Chol liposomes, at the (4/1) (+/-) charge ratio, was the most efficient to mediate gene delivery, even in the presence of serum. The simultaneous addition of vinblastine and HSA-EPOPC:Chol/DNA (+/-) (4/1) lipoplexes to TSA cells improved transgene expression more than 10 times. When combined with the HSV-Tk/GCV "suicide" gene therapy mediated by HSA-EPOPC:Chol/DNA (+/-) (4/1) lipoplexes, vinblastine induced a great enhancement in the antitumoral activity in TSA cells. Most importantly, this combined strategy resulted in a significant synergistic effect, thus allowing the use of a much lower dose of the drug to achieve the same therapeutic effect. Overall, our results indicate that this approach has the potential to overcome some major limitations of conventional chemotherapy, and may therefore constitute a promising strategy for future applications in antitumoral therapy.